Green Strategies for the Preparation of Enantiomeric 5–8-Membered Carbocyclic β-Amino Acid Derivatives through CALB-Catalyzed Hydrolysis - Sayeh Shahmohammadi; Tünde Faragó; Márta Palkó; Enikő Forró (Molecules, 2022)
Candida antarctica lipase B-catalyzed hydrolysis of carbocyclic 5–8-membered cis β-amino esters was carried out in green organic media, under solvent-free and ball-milling conditions. In accordance with the high enantioselectivity factor ( E > 200) observed in organic media, the preparative-scale resolutions of β-amino esters were performed in t BuOMe at 65 °C. The unreacted β-amino ester enantiomers (1 R ,2 S ) and product β-amino acid enantiomers (1 S ,2 R ) were obtained with modest to excellent enantiomeric excess ( ee ) values ( ee s > 62% and ee p > 96%) and in good chemical yields (>25%) in one or two steps. The enantiomers were easily separated by organic solvent/H 2 O extraction.